Review Article: Phytochemical And Pharmacological Study Of Teapot Grass (Cyperus Rotundus L) As A Medicinal Plant - Sudirman, Suharni (Hayyan Journal, 2024)
This research is a literature study. The purpose of this study is to determine the chemical content contained in teki grass and its medicinal potential, increase the use of teki grass as a traditional medicine by conducting more systematic and scientific research, and find alternative traditional medicines that are effective and safe for various diseases. This research was prepared using the literature study method. The data collection process was carried out with a literature study on relevant articles and related to the phytochemical study of teki grass plants and the development of its parts that can be utilized. The journal review process involved analyzing relevant articles, with a focus on empirical research conducted within the last 10 years. The search for articles and some data was conducted using Google Scholar and Chat Gpt academic data. Previous phytochemical studies on teki grass tubers revealed the presence of alkaloids, flavonoids, tannins, starch, glycosides and furochromones, and sesquiterpenoids. In the phytochemical test, it was found that teki grass contained alkaloids, saponins, flavonoids, tannins, essential oils and sesquiterpenoids. These compounds are found in parts of the teki grass plant such as leaves, and tubers. Teapot grass plants also have pharmacological activities as wound healing, anti-inflammatory, antimicromial, antibacterial, antioxidant and analgesic activities.